Failure behavior and mechanical properties of prefabricated cantilever retaining under dynamic effect - Du, Yihan; Du, Xuze; Han, Wei; Huang, Bo; Huang, Songtao; Liang, Peng; Zhang, Mo (Frontiers in Built Environment, 2024)
Prefabricated retaining wall is in line with the development trend of greening and environmental protection of civil engineering, and has a broad application prospect. However, the seismic response of prefabricated retaining wall has not been systematically revealed. Therefore, in this study, a simple fabricated cantilever retaining wall with connecting plate was proposed, and the mechanical properties of prefabricated cantilever retaining under dynamic effect was investigated by the experimental and numerical methods. At first, the physical model experiments of prefabricated cantilever retaining with different vertical plate thicknesses were carried out. Subsequently, the mechanical properties of the prefabricated cantilever retaining were investigated. The research results show that the thickness of retaining wall significantly affects the failure pattern, the larger the thickness, the more complete the broken pattern. In addition, the connection between the vertical plate and the bottom plate is prone to cracks induced by stress concentration, eventually leading to damage. As the thickness of the vertical plate increases, the top stress of the vertical plate decreases but the bottom stress increases. The greater the embedded depth of the vertical plate, the larger the stress and displacement at bottom of the vertical plate. The larger the longitudinal length of the retaining wall, the smoother the stress distribution curve of the vertical plate, and the smaller the compressive stress at the bottom. Furthermore, the effect of concrete strength on mechanical properties is not obvious. This study provides an idea for the dynamic response research of prefabricated retaining structure.